The impact of the COVID-19 pandemic on engagement in activities of daily living in persons with acquired brain injury. (28th January 2022) - Goverover, Yael; Kim, Grace; Chen, Michelle H.; Volebel, Gerald T.; Rosenfeld, Meirav; Botticello, Amanda; DeLuca, John; Genova, Helen M.
ABSTRACT: Primary Objectives: This study examined (a) the impact of coronavirus disease-2019 (COVID-19) pandemic on engagement in activity participation in persons with acquired brain injury (ABI); and (b) whether changes in activity participation during the pandemic were associated participants' health-related quality of life (HRQoL). Research Design: Exploratory online survey study. Methods: Eighty-seven respondents with ABI and 98 healthy adults (HA) participated in this study. Engagement in activity participation during COVID-19 was calculated as a percentage of the activities participants performed before the pandemic. Main Results: Participants with ABI modified their activities less than HA in order to maintain level of engagement in activity participation. They stopped performing more activities during the pandemic compared to HA and compared to their pre-pandemic engagement. Both groups continued to do similar percentage of activities without modifications compared to before the pandemic. Better HRQoL in both groups was predicted by a larger percentage of activities continued and fewer activities stopped. Conclusion: Results emphasize the importance of addressing activity participation changes during situations where there are disruptions of the individual's habits and routines in order to minimize negative consequences of such changes.